Role of Micro Credit Program in Empowering Rural Women in Bangladesh: A Study on Grameen Bank Bangladesh Limited - Kumar, Dhanonjoy; Hossain, Afjal; Gope, Monto Chandra (Asian Business Review, 2013)
Bangladesh is one of the high density countries of the world. 40% of its population lives below the poverty level of which rural women are poorer. The rise of the Micro Credit Institution in the global context is identified as an important phenomenon which has implication for the development prospects of the poor. The paper was designed to identify the role of Grameen Bank (GB) and to analyze rural women’s economic empowerment as the outcome of micro-credit interventions. In this regard, an exploratory research has been made to focus on the activities and impacts after receiving micro-credit from GB. A sample size of 100 respondents has been interviewed through a structured questionnaire, in-depth interview and observation from Jhenaidah and Kushtia districts. The result shows that the women are more independent and can engage in decision making process after receiving and using micro credit.JEL Classification Code:  M19